2022
DOI: 10.7717/peerj.12708
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical profile in mixed martial arts athletes

Abstract: The study aimed to evaluate changes in selected biochemical indicators among mixed martial arts competitors in subsequent periods of the training cycle. The research involved 12 mixed martial arts athletes aged 25.8 ± 4.2 years competing in the intermediate category. Selected somatic indicators were measured twice. Biochemical indicators were assessed five times during the 14-week study period. Serum concentrations of testosterone, cortisol, uric acid, myoglobin, total protein, interleukin 6, and tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(53 reference statements)
0
12
0
7
Order By: Relevance
“…The lack of a clear understanding of the overall strategy for optimizing the comprehensive control system in mixed martial arts is one of the controversial issues for scientists in physical education and sports physiology ( James et al, 2016a ; James et al, 2016b ; Kirk et al, 2021 ; Chernozub et al, 2019 ; Tota & Wiecha, 2022 ). One of the directions of this problem is related to the need to identify the most informative criteria for assessing the adaptive body changes in MMA athletes of strike fighting style and to find effective regimes of power training in the process of special training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of a clear understanding of the overall strategy for optimizing the comprehensive control system in mixed martial arts is one of the controversial issues for scientists in physical education and sports physiology ( James et al, 2016a ; James et al, 2016b ; Kirk et al, 2021 ; Chernozub et al, 2019 ; Tota & Wiecha, 2022 ). One of the directions of this problem is related to the need to identify the most informative criteria for assessing the adaptive body changes in MMA athletes of strike fighting style and to find effective regimes of power training in the process of special training.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the structure of complex control in martial arts, a number of researchers ( Chernozub et al, 2019 ; Kirk et al, 2021 ; Tota & Wiecha, 2022 ) found out that changes in biochemical indicators of blood were the most informative markers of adaptation compensatory reactions of athletes to stressful physical stimuli. Taking into account the complexity and high cost of conducting comprehensive biochemical blood tests to study adaptation processes in different training load regimes, most leading experts in biology and sports ( Marques et al, 2017 ; Philippou et al, 2017 ; Wochyński & Sobiech, 2017 ) used only a small number of markers (2–4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Однією з актуальних та одночасно не до кінця вирішених проблем дослідження ефективних механізмів удосконалення тренувального процесу в змішаних єдиноборствах під час спеціальної підготовки, є визначення особливостей впливу різних за інтенсивністю навантажень та обсягом роботи на рівень тренованості спортсменів [4,5,6]. Одночасно, відкритим залишається питання дослідження характеру адаптаційних змін в організмі спортсменів ММА та інших єдиноборств в умовах м'язової діяльності з використанням анаеробних (лактатних та алактатних) та аеробних режимів енергозабезпечення, особливо в поєднані з різними параметрами компонентів силового навантаження [7,8,9].…”
unclassified